Adobe InDesign CS5 learn by video - Viers, Russel (Berkeley, CA Peachpit Press [in association with Adobe Press], 2011)
Learn the fundamentals of Adobe InDesign CS5 as well as the basic principles of page layout design. Learn how to use essential tools to design, layout, preflight, and publish engaging print documents or add interactivity and publish them online.
What's new in InDesign CS5? -- Using GREP in InDesign CS5. DVD contents: Introduction -- The InDesign environment -- The interactive tools panel -- Working with documents -- Working with pages -- Working with text -- Working with graphics -- Refining documents -- Working with objects -- Managing page elements -- Working with tables -- Finalizing documents.
System requirements: Microsoft Windows XP/Vista/7; Max OS X; Linux; 512 MB RAM; display resolution 1024x768 or higher.
Keywords: Adobe InDesign (Electronic resource).; Desktop publishing